Pengaruh Likuiditas, Solvabilitas dan Profitabilitas Terhadap Kinerja Keuangan Pada Perusahaan Sub Sektor Otomotif dan Komponen Yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2020-2022 - Mochammad Irfan Saputra; Fauzan Akbar Albastiah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Financial performance of a company refers to the financial results achieved from various actions taken during a specific period. These activities are recorded and summarized into data that can be used to explain the company's condition and position to relevant parties. To benefit from this process, a company requires solid and profitable financial performance. This research aims to analyze the influence of liquidity, solvency, and profitability on the financial performance of companies in the automotive and component subsector listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022. The analysis method used is multiple linear regression analysis with a sample of nine companies selected using purposive sampling method. The data used is secondary data obtained from financial reports of companies published on the Indonesia Stock Exchange (IDX). The data were processed using Statistical Product Service Solution (SPSS) 29. The results of this study indicate that liquidity has a nonsignificant positive effect on Financial Performance. Leverage does not affect Financial Performance. Profitability has a significant positive effect on Financial Performance. Liquidity, Leverage and Profitability have a significant effect on Financial Performance